2013
DOI: 10.1063/1.4829482
|View full text |Cite
|
Sign up to set email alerts
|

Secondary instability of roughness-induced transient growth

Abstract: Calculations are performed to analyze the stability of steady roughness-induced transient growth to unsteady fluctuations. The basic states consist of an optimal transient growth model and a previously computed direct numerical simulation that fully resolves the three-dimensional roughness element. It is shown that sub-optimal transient growth produced by surface roughness is much more susceptible to destabilization than optimal perturbation predictions. The factors contributing to this behavior are analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…As can be seen, all the modes are mostly localised along the central low-speed region, differently from the case of non-isolated cylinder analysed in the previous section for which a large part of the mode migrates on the outer streaks downstream of the roughness element. The crucial importance of such low-speed regions in the roughness-induced transition process to turbulence has already been underlined by previous studies such as the experimental work by Asai et al (2002Asai et al ( , 2007, or the numerical investigation by Brandt (2007) and Denissen & White (2013). More recently, several different authors have observed a similar behaviour in the case of roughness-induced compressible boundary layer flows (Bernardini et al 2012;Balakumar & Kegerise 2013;Iyer & Mahesh 2013;de Tullio et al 2013;Subbareddy et al 2014).…”
Section: Influence Of the Aspect Ratiosupporting
confidence: 55%
See 1 more Smart Citation
“…As can be seen, all the modes are mostly localised along the central low-speed region, differently from the case of non-isolated cylinder analysed in the previous section for which a large part of the mode migrates on the outer streaks downstream of the roughness element. The crucial importance of such low-speed regions in the roughness-induced transition process to turbulence has already been underlined by previous studies such as the experimental work by Asai et al (2002Asai et al ( , 2007, or the numerical investigation by Brandt (2007) and Denissen & White (2013). More recently, several different authors have observed a similar behaviour in the case of roughness-induced compressible boundary layer flows (Bernardini et al 2012;Balakumar & Kegerise 2013;Iyer & Mahesh 2013;de Tullio et al 2013;Subbareddy et al 2014).…”
Section: Influence Of the Aspect Ratiosupporting
confidence: 55%
“…It is worthy to note finally that, relatively far from the roughness element, the shapes of these global modes visualized in different X = constant planes are very similar to that found by Brandt (2007) and more recently by de and Denissen & White (2013) using a local stability approach. Indeed, due the strong predominance of the base flow streamwise component and its nearly parallel nature far from the roughness element, it is expected that the two approaches, global and local, give similar results regarding the shape of the modes in the almost parallel parts of the flow.…”
Section: Analysis Of the Modessupporting
confidence: 51%
“…Biglobal stability analysis to investigate roughness wakes in planes perpendicular to the main flow was mainly used in supersonic boundary layers, see, e.g. Groskopf, Kloker & Marxen (2010); recent studies for subsonic boundary-layer flow are reported by Denissen & White (2013) and Shin, Rist & Krämer (2015). The two-dimensional unstable eigenfunctions were either of varicose or sinuous type, where a dominant varicose mode could be connected to the three-dimensional shear layer developing downstream of the roughness.…”
Section: Introductionmentioning
confidence: 98%
“…Alternatively, surface roughness or a wing-fuselage junction may generate perturbations in the boundary layer. While Fransson et al (2004) and White, Rice & Gökhan Ergin (2005) suggest that such perturbations do not have the character of optimal perturbations, they were shown to be even less stable than optimal ones and to exhibit secondary instability for lower streak amplitudes (Denissen & White 2013). Meneghello, Schmid & Huerre (2015) demonstrate that a strong receptivity is observed in particular for perturbations applied in the immediate vicinity of the attachment line.…”
mentioning
confidence: 97%